Fracture Characteristics of Sliding Crack in Brittle Rock: Analysis Based on an Improved Equivalent Crack Model - Zhang, Yin; Cui, Shenghua; Yu, Zhibing; Cheng, Jianlong (Frontiers in Earth Science, 2022)
Under low confinement axial compression, the failure of brittle rock is mainly caused by tensile fracture. Many scholars adopt the sliding crack as an idealized model to present the intrinsic mechanism of the tensile failure, but lack rigorous demonstrations on how the sliding crack affects the deformation and failure of brittle rocks. In this paper, an improved model of sliding crack is proposed, in the context of linear elastic fracture mechanics (LEFM) and weight function method, the expression of stress intensity factor (SIF) has been derived. The propagation manners of sliding crack under axial loading and lateral unloading conditions have been further analyzed. Extended finite element method (XFEM) is employed to verify the correctness of the theoretical SIF formulation and its inferences. The fracture analysis shows that sliding crack is highly sensitive to the change of the lateral stress, which theoretically explains compressive failure characteristics of brittle rock: (1) Under the condition of axial compression, increasing the lateral stress has a very strong no-linear impact on the strength of brittle rock; (2) Under the condition of lateral unloading, the destruction of rock is more abrupt and ferocious than that of the loading case. In order to confirm that micro-fractures in rocks are notably influenced by confining pressure, as the former theoretical fracture analysis predicted, tri-axial compression test combined with acoustic emission monitoring technique has been conducted on basalt samples. According to acoustic waveform parameter method, it shows that increasing the confining pressure will greatly reduce the proportion of tension-type fractures, which indirectly proves the correctness of sliding crack hypothesis and fracture analysis.